دور التظلم الإداري في تسوية المنازعات الضريبية - العانز نصر الدين, نصر الدين; مهاجر بلال, بلال; قيس, كرام (University of Eloued جامعة الوادي, 2023)
تعتبر المرحلة الإدارية في تسوية المنازعات الضريبية مرحلة حاسمة وضرورية اوجبها المشرع الجبائي أولا للمكلف قبل التوجه الى الجهات القضائية الإدارية المختصة، وذلك من اجل الحصول على حقه او الدفاع عنه، وهي في نفس الوقت تعتبر وسيلة لكي تقوم الإدارة الضريبية بتصحيح اخطائها المرتكبة اثناء فرضها للضريبة وتقديرها، فمتى كانت هذه الضريبة المفروضة على المكلف والإجراءات المتبعة في تحصيلها من قبل الإدارة متعسفة ومجحفة في حق المكلف بها وجب عليه الطعن فيها امام نفس الجهة الصادرة عنها، وذلك من خلال تقديم شكوى ( تظلم اداري مسبق ) والتي تتطلب توفر مجموعة من الشروط والإجراءات المنصوص عليها قانونا. وفي حالة عدم رضا المكلف بقرار مدير الضرائب بالولاية يمكنه اللجوء الى جهة إدارية أخرى يتم تقديم الطعن امامها والمتمثلة في لجان الطعن الإدارية، وذلك من اجل تصحيح الأخطاء المرتكبة في الوعاء الضريبي او الاستفادة من حكم تشريعي او تنظيمي، وبالرغم من الدور الكبير الذي تلعبه هذه اللجان في حل النزاع الضريبي القائم الا انها لم تلقى صدى او اقبال كبير من طرف المكلفين، ولأنه تم احداثها مؤخرا لم يعرف بوجودها الكثير منهم، والسبب الرئيسي لعدم الاقبال الكبير اليها راجع الى الآراء الغير الزامية التي تصدرها، كما ان اللجوء اليها اختياري وليس وجوبي وهذا كسبب اخر لعدم التوجه اليها للطعن امامها. THE ADMINISTRATIVE STAGE IN SETTLING TAX DISPUTES IS A CRUCIAL AND NECESSARY ONE WHICH IS IMPOSED BY THE TAX LEGISLATOR FOR THE TAXPAYER, AT THE FIRST PLACE, BEFORE EVEN GOING TO THE COMPETENT ADMINISTRATIVE JUDICIALAUTHORITIES IN ORDER TO OBTAIN OR DEFEND HIS RIGHT. AT THE SAME TIME, IT IS CONSIDERED AS A MEANS FOR THE TAX ADMINISTRATION TO CORRECT ITS MISTAKES MADE DURING THE IMPOSITION AND ASSESSMENT OF THE TAX. SO, WHENEVER THIS TAX IMPOSED ON THE TAXPAYERS AND THE PROCEDURES FOLLOWED IN ITS COLLECTION BY THE ADMINISTRATION ARE ARBITRARY AND UNFAIR AGAINST THE TAXPAYERS, HE/SHE MUST APPEAL IT BEFORE THE SAME AUTHORITY ISSUING IT BY FILING A COMPLAINT (ADVANCE ADMINISTRATIVE GRIEVANCE) WHICH REQUIRES THE FULFILLMENT OF A SET OF CONDITIONS AND PROCEDURES STIPULATED BY LAW. IN CASE THAT THE TAXPAYERS ARE NOT SATISFIED WITH THE DECISION OF THE STATE TAX DIRECTOR. HE CAN RESORT TO ANOTHER ADMINISTRATIVE BODY BEFORE WHICH THE APPEAL IS SUBMITTED, REPRESENTED BY THE ADMINISTRATIVE APPEAL COMMITTEES, IN ORDER TO CORRECT THE ERRORS COMMITTED IN THE TAX BASE OR BENEFIT FROM A LEGISLATIVE OR REGULATORY RULING. DESPITE THE GREAT ROLE PLAYED BY THESE COMMITTEES IN RESOLVING THE EXISTING TAX DISPUTE, THEY DID NOT RECEIVE A GREAT RESPONSE OR TURNOUT FROM THE TAXPAYERS. THIS WAS BECAUSE THEY WERE CREATED RECENTLY, AND MANY OF THEM DID NOT KNOW ABOUT THEIR EXISTENCE. IN ADDITION, THE MAIN REASON FOR THE LACK OF GREAT TURNOUT FOR THEM IS DUE TO THE NON-BINDING OPINIONS THEY ISSUE. ALSO, RESORTING TO THEM IS OPTIONAL AND THIS IS ANOTHER REASON WHY TAXPAYERS DID NOT GO TO THEM TO MAKE AN APPEAL.
مذكرة ماستر
Keywords: المنازعات الضريبية , الوعاء الضريبي , الشكاية ( التظلم الإداري ) , لجان الطعن الإدارية , التحصيل الضريبي , التحصيل الودي , التحصيل الجبري , الطعن العفوي .; TAX DISPUTES،TAK BASE، THE COMPLAINT، ADMINISTRATIVE APPEALCOMMITTES،TAX COLLECTION, AMIABLE COLLECTION،FORCED COLLECTION،SPONTANEOUSAPPEAL.